Gregor Samsa’s Self Alienation in Franz Kafka’s Metamorphosis: Lacanian Psychoanalysis - Devicha Lidya Asriningtyas; Ali Mustofa (Humanitatis : Journal of Language and Literature, 2022)
This research is focused on Jacques Lacan's psychoanalytic theory, which is described in the main character in Franz Kafka's novel The Metamorphosis. Gregor Samsa is the main character of The Metamorphosis. Gregor was a traveling salesman who was the Samsa family's sole son and earner. He mysteriously transforms into a massive bug, causing him to be estranged from his family. The author finds out why Gregor’s family members do not care about him and can't perceive him as a complicated human being with his own needs. As a result, Gregor has been estranged from his family and himself. The author argues that Gregor has another alienation from his physical reality after the transformation. His family views him as a terrifying, unpleasant monster, as seen by their fear of his existence and their decision to get rid of him. Gregor, who suffers from humiliation, views himself in the same light. He and his family unwittingly reject Gregor's potential as an individual, making him feel alienated. This research aims to identify how Gregor's conditions make him feel alienated and the connection between his identity crisis and alienation, as depicted in The Metamorphosis. Although humans are free human beings, society contributes to the perspective of self-identity and the decision of their own goals.